Implications of Economic Globalization on Labor Market Policies: A Comparative Study of the Philippines and Indonesia - Viajar, Verna Dinah Q. (Philippine Political Science Journal; Vol 30 No 53 (2009), 2009)
This essay examines the implications of economic globalization on the labor markets in the Philippines and Indonesia. Today's economic globalization characterized by liberalization of the market, privatization of state-owned enterprises, and minimal government intervention in the economy, results in job losses, retrenchments and irregular employment and rising wage differentials among workers. Both countries follow liberal economic policies that have constrained the state's response in terms of labor market policies to mitigate the negative impact of economic globalization. Free market proponents consider as labor rigidities the state's policy interventions in the labor market and the participation of trade unions. Labor flexibility and the free interplay of labor supply and demand are the ones valued in the liberalized labor market. Though constrained and weakened to address the economic restructuring brought about by globalization, the labor movements in the Philippines and Indonesia continue to find ways to develop new unionisms and strategies to organize themselves as social movements.